Cerebral schistosomiasis in a 3-year-old girl due to Schistosoma japonicum: a case report - Guo, Yangyang; Zhang, Jindong; Chai, Ruichao; Yang, Yanlin; Tian, Kaibing; Shi, Guangzhi; Zhang, Linlin (Frontiers in Immunology, 2024)
IntroductionCerebral schistosomiasis is a rare but severe manifestation of Schistosoma japonicum infection, often leading to significant neurological impairment. This case report details the clinical presentation, diagnostic challenges, and treatment of a 3-year-old girl with cerebral schistosomiasis in Sichuan, China.Case descriptionA 3-year-old girl from a rural area in Sichuan, China, presented with a 3-month history of unstable walking, left facial paralysis, drowsiness, and intermittent fever. Brain MRI revealed giant polycystic lesions in the right temporal, parietal, and occipital lobes, suggestive of an abscess with ependymitis. Despite no history of travel to endemic areas or known freshwater exposure, the patient was diagnosed with cerebral schistosomiasis due to Schistosoma japonicum based on histological examination and metagenomic next-generation sequencing (mNGS) of brain tissue obtained through surgery. The patient underwent surgical resection of the lesions and received two courses of praziquantel combined with corticosteroids and anticonvulsants. Despite residual left-sided hemiplegia, her cognitive function remained comparable to that of her peers, and no recurrence of the disease was observed over three years of follow-up.ConclusionThis case underscores the diagnostic challenges of cerebral schistosomiasis, particularly in non-endemic areas or in the absence of a clear history of freshwater exposure. Early surgical intervention combined with praziquantel treatment can lead to favorable outcomes, even in severe cases with extensive brain involvement.